Lexical addition in American Sign Language - Steinbergs, Aleksandra; O’Dea, Barbara (Papers from the Annual Meetings of the Atlantic Provinces Linguistic Association (PAMAPLA) / ACTES DES COLLOQUES ANNUELS DE L’ASSOCIATION DE LINGUISTIQUE DES PROVINCES ATLANTIQUES (ACAALPA)., 1990)
This paper explores the methods which ASL uses to add new signs to its lexicon. We show that ASL adds lexical items by utilizing both native and borrowed elements: native signs are used in the processes of compounding, affixation, reduplication, and metaphorical extension, while borrowed elements are loan signs which derive from finger-spelled English words. As in the case of spoken languages, ASL has phonotactic constraints on the form of lexical items, according to which all new signs are modified. We conclude that, despite the obvious differences between the media of communication, the methods used by ASL to create new lexical items are strikingly similar to those used by spoken languages.